The Influence of Marketing Mix and Service Quality on Purchase Decisions of Dreys Corner Coffee Products - Magdalena; Hendy Tannady; Siti Nurjanah (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine how much influence the purchase decision at a coffee shop, so it needs a marketing mix, as well as good service, so as to be able to provide purchasing decisions to consumers. This research is a quantitative approach using the SPSS Static 25 program with a sample size of 130 respondents who have bought and visited Dreys Corner Coffee. by using nonprobability sampling and purposive techniques. The results of the T test showed that the price, place, and service quality variables significantly influence purchasing decisions. Meanwhile, product and promotion variables do not significantly influence purchasing decisions. The benefit of this research for Dreys Corner Coffee is to increase product and promotion so that they can compete with other competitors.